2020
DOI: 10.1161/jaha.119.014447
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Very Elderly Patients Aged ≥90 With Acute Ischemic Stroke

Abstract: Background Patients aged ≥90 were excluded or under‐represented in past thrombectomy trials; thus, uncertainty remains whether treatment benefits can be expected regardless of age. This study investigates outcome and safety of thrombectomy in nonagenarians to improve decision making in a real‐world setting. Methods and Results All currently available data of patients aged ≥90 enrolled in the GSR‐ET (German Stroke Registry–Endovascular Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 25 publications
2
36
0
Order By: Relevance
“…Very recently, an analysis of German Stroke Registry-Endovascular Treatment showed that patients aged ≥90 years have higher mortality for thrombectomy. 25 Decision-making for thrombectomy in patients aged ≥90 years should be premised on a case-by-case basis with regard to admission NIHSS and ASPECT scores.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, an analysis of German Stroke Registry-Endovascular Treatment showed that patients aged ≥90 years have higher mortality for thrombectomy. 25 Decision-making for thrombectomy in patients aged ≥90 years should be premised on a case-by-case basis with regard to admission NIHSS and ASPECT scores.…”
Section: Discussionmentioning
confidence: 99%
“…The median patient age was 73 years (IQR, 69-78 years), and the median baseline NIHSS score was 17 (IQR, [13][14][15][16][17][18][19][20][21][22]. Of the 482 enrolled patients, 259 (53.73%) were men and 392 (81.33%) had anterior circulation stroke.…”
Section: Resultsmentioning
confidence: 99%
“…15 In contrast, some studies have revealed no association of IVT pre-treatment prior to MT with prognosis in elderly patients. [16][17][18] It is important to note that those studies were not designed to compare the effects of direct MT and bridging MT. Furthermore, some of those studies were not multicenter studies.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Even for nonagenarians multiple studies evaluating thrombectomy have shown promising results. 27 , 28 In a recent analysis including 124 nonagenarians from the ETIS Registry, patients with successful reperfusion had lower 90-day mRS compared to non-recanalized patients. Moreover, patients with successful reperfusion after one pass had reduced 90-day mortality and increased odds of good outcome (mRS score ⩽3).…”
Section: Borderline Indications For Evtmentioning
confidence: 99%